Atezolizumab and nab-Paclitaxel in Advanced Triple-Negative Breast Cancer: Biomarker Evaluation of the IMpassion130 Study. (1st February 2021) - Emens, Leisha A; Molinero, Luciana; Loi, Sherene; Rugo, Hope S; Schneeweiss, Andreas; Diéras, Véronique; Iwata, Hiroji; Barrios, Carlos H; Nechaeva, Marina; Nguyen-Duc, Anh; Chui, Stephen Y; Husain, Amreen; et al.
Abstract: Background: Understanding the impact of the tumor immune microenvironment and BRCA1/2- related DNA repair deficiencies on the clinical activity of immune checkpoint inhibitors may help optimize both patient and treatment selection in metastatic triple-negative breast cancer. In this substudy from the phase 3 IMpassion130 trial, immune biomarkers and BRCA1/2 alterations were evaluated for association with clinical benefit with atezolizumab and nab -paclitaxel (A+nP) vs placebo and nP in unresectable (P+nP) locally advanced or metastatic triple-negative breast cancer. Methods: Patients were randomly assigned 1:1 to nab -paclitaxel 100 mg/m 2 (days 1, 8, and 15 of a 28-day cycle) and atezolizumab 840 mg every 2 weeks or placebo until progression or toxicity. Progression-free survival and overall survival were evaluated based on programmed death-ligand 1 (PD-L1) expression on immune cells (IC) and tumor cells, intratumoral CD8, stromal tumor-infiltrating lymphocytes, and BRCA1/2 mutations. Results: PD-L1 IC+ in either primary or metastatic tumor tissue was linked to progression-free survival and overall survival benefit with A+nP. PD-L1 IC+ low (26.9%; 243 of 902 patients) and high (13.9%; 125 of 902 patients) populations had improved outcomes that were comparable. Intratumoral CD8 and stromal tumor-infiltrating lymphocytes positivity (sTIL+) were associated with PD-L1 IC+ status; improved outcomes were observed with A+nP vs P+nP only in CD8+ and sTIL+ patients who were also PD-L1 IC+. BRCA1/2 mutations (occurring in 14.5% [89 of 612 patients]) were not associated with PD-L1 IC status, and PD-L1 IC+ patients benefited from A+nP regardless of BRCA1/2 mutation status. Conclusions: Although A+nP was more efficacious in patients with richer tumor immune microenvironment, clinical benefit was only observed in patients whose tumors were PD-L1 IC+.